Jamesian pragmatism: a framework for working towards unified diversity in nursing knowledge development - McCready, Jason S. (Nursing philosophy, 2010)
Nursing is frequently described as practical or pragmatic and there are many parallels between nursing and pragmatism, the school of thought. Pragmatism is often glancingly referenced by nursing authors, but few have conducted in-depth discussions about its applicability to nursing; and few have identified it as a significant theoretical basis for nursing research. William James's pragmatism has not been discussed substantially in the nursing context, despite obvious complementarities. James's theme of pluralism fits with nursing's diversity and plurality; his emphasis on social conscience in our actions matches nursing's fundamental purpose of improving the lives of others; his continuous testing of pluralistic truths in critically reflective practice pairs well with nursing's focus on developing best-available, holistic evidence; and his conceptualization of truth as being born in practice and becoming an instrument in practice is entirely compatible with nursing's theory-practice identity. The oft-discussed theory-practice gap is seen to hinder the development of nursing knowledge. If nursing is to find its identity in knowledge development and potentiate the knowledge developed, it is imperative to identify and address that which is impeding progress. By way of the pragmatic tenets of William James, I will argue that a significant part of the theory-practice gap lies in how nursing knowledge development is operationalized, creating a false dichotomy between practice and research. I will also argue that the research-practice schism has been widened by continued philosophical and methodological infighting in the research community. I will describe how Jamesian pragmatism can be ‘what works’ for rebuilding relationships and supporting an engaged plurality within nursing research and bring research and practice together into a collaborative and iterative process of developing nursing knowledge.